On the Border in Northern Mauritania - Mark Drury (L’Année du Maghreb)
This paper considers what the northern Mauritanian border reveals about territory, mobility and belonging across the region of western Sahara. Historical examples trace a shift from a relatively permeable frontier zone during colonialism to an increasingly fixed border during decolonization. Ethnographic examples from the border crossing of Guerguerat and the northern Mauritanian town of Nouadhibou connect to recent developments during which the northern Mauritanian border has become a flashpoint in the Western Sahara conflict. Together, these examples show the significance of the northern Mauritanian border to social processes of value production, as well as political processes of subject formation across western Sahara. In focusing on historical shifts as well as contemporary, quotidian interactions, this paper highlights the uneven and changing effects of the northern Mauritanian border over time and across space, and its pivotal role in producing and reproducing disjunctures between people, territory and sovereignty across the region, particularly since decolonization.